2004
DOI: 10.1136/jnnp.2003.025957
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic visual search training: a treatment for patients with homonymous hemianopia

Abstract: Objectives: We describe a novel rehabilitation tool for patients with homonymous hemianopia based on a visual search (VS) paradigm that is portable, inexpensive, and easy to deploy. We hypothesised that by training patients to improve the efficiency of eye movements made in their blind field their disability would be alleviated. Methods: Twenty nine patients with homonymous visual field defects (HVFD) without neglect practised VS paradigms in 20 daily sessions over one month. Search fields comprising randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(140 citation statements)
references
References 21 publications
6
130
1
3
Order By: Relevance
“…17 To this end, evaluation of features of scan paths as a base for eye movement strategies was reported. 18 Another example is saccadic visual search training 19 and optokinetic therapy. 20 An obvious limitation of our study is its observational character, ie, we are lacking a control group of untreated hemianopes.…”
Section: Discussionmentioning
confidence: 99%
“…17 To this end, evaluation of features of scan paths as a base for eye movement strategies was reported. 18 Another example is saccadic visual search training 19 and optokinetic therapy. 20 An obvious limitation of our study is its observational character, ie, we are lacking a control group of untreated hemianopes.…”
Section: Discussionmentioning
confidence: 99%
“…Even the majority of computer-based training is either completed in clinic 16,17 or at home with therapist supervision 20,22,23 , although one recent study has demonstrated that a web-based reading training can increase reading speed in patients with right-sided HVFDs 27 . Whether it is the patient regards to exploration and reading 22,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Although few studies have evaluated such therapy relative to a control intervention, several studies have reported significant benefits following compensatory training such as improved exploration, more efficient saccadic behaviour and subjective improvements in activities of daily living (ADL) [16][17][18][19][20][21][22][23] . Specific compensatory reading training has also been developed and positive effects reported [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…One strategy to compensate for a lateralized field deficit is to saccade as far into the blind field as possible to maximise the proportion of the search area that falls in the sighted field (Pambakian, Currie, & Kennard, 2005;Pambakian, Mannan, Hodgson, & Kennard, 2004). Encouraging patients to utilize these strategies in real life improves general functioning (based on selfreports, Mannan, Pambakian, & Kennard, 2010;Zihl, 1981).…”
mentioning
confidence: 99%